The Role of Islamic Family Law in Modern Child Custody Cases: Balancing Sharia Principles with Contemporary Needs - Safii, Nur Muhammad; Kaur, Gagandeep (Journal of Islamic Family Law, 2025)
Islamic Family Law has been widely used in the field of child custody, balancing traditional Sharia principles with contemporary child welfare needs. This study, therefore, aims to provide a comprehensive analysis of the role of Islamic family law in modern child custody cases, specifically focusing on how traditional values can be integrated with modern child welfare concerns. This research uses a qualitative research approach to explore the intersections between Islamic family laws and contemporary family dynamics, including the Qur'an and Hadith, as well as classical jurisprudential interpretations from major Islamic schools of thought. Thematic analysis is used to identify recurring themes and patterns related to Islamic legal principles in custody cases and the influence of modern legal standards and the impact of social changes on custody practices. The analysis also uncovers significant challenges in cases involving divorced or separated parents residing in different countries. The study concludes that the integration of traditional child welfare standards, such as prioritizing the child's emotional health, educational needs, and, where appropriate, considering the children's preference, enhances the applicability of Islamic Family law in addressing complex custody issues. This situation brings to light the importance of understanding how Islam can be harmonized with secular laws to provide solutions for Muslim families living in non-Muslim societies, especially when navigating child custody issues that are both legally and religiously sensitive.